Leanness and Low Plasma Leptin in GPR17 Knockout Mice Are Dependent on Strain and Associated With Increased Energy Intake That Is Not Suppressed by Exogenous Leptin - Wargent, Edward T.; Ahmad, Suhaib J. S.; Lu, Qing Richard; Kostenis, Evi; Arch, Jonathan R. S.; Stocker, Claire J. (Frontiers in Endocrinology, 2021)
Previous studies have shown that agonists of GPR17 stimulate, while antagonists inhibit feeding. However, whole body knockout of GPR17 in mice of the C57Bl/6 strain did not affect energy balance, whereas selective knockout in oligodendrocytes or pro-opiomelanocortin neurons provided protection from high fat diet-induced obesity and impaired glucose homeostasis. We reasoned that whole body knockout of GPR17 in mice of the 129 strain might elicit more marked effects because the 129 strain is more susceptible than the C57Bl/6 strain to induction of uncoupling protein-1 expression in white adipose tissue and less susceptible to high fat diet-induced obesity. Consistent with this hypothesis, compared to wild-type mice, and when fed on either a chow or a high fat diet, GPR17 -/- mice of the 129 strain displayed increased expression of uncoupling protein-1 in white adipose tissue, lower body weight and fat content, reduced plasma leptin, non-esterified fatty acids and triglycerides, and resistance to high fat diet-induced glucose intolerance. Not only energy expenditure, but also energy intake was raised. Administration of leptin did not suppress the increased food intake in GPR17 -/- mice of the 129 strain, whereas it did suppress food intake in GPR17 +/+ mice. The only difference between GPR17 /- and GPR17 +/+ mice of the C57Bl/6 strain was that the body weight of the GPR17 -/- mice was lower than that of the GPR17 +/+ mice when the mice were fed on a standard chow diet. We propose that the absence of GPR17 raises sympathetic activity in mice of the 129 strain in response to a low plasma fuel supply, and that the consequent loss of body fat is partly mitigated by increased energy intake.